The mediating role of emotion regulation in the relationship between attachment styles and social skills and anxiety in children with autism spectrum disorder - ali Kareem Khlaif Al-Shammar; khodamorad momeni; kamran yazdanbaksh (مجله علوم روانشناختی)
Background: Autism Spectrum Disorder (ASD) is one of the most complex developmental disorders, affecting children's cognitive, emotional, and social abilities. Emotion regulation and attachment styles are critical factors that can directly influence social skills and anxiety levels in children with this disorder. Despite numerous studies on ASD, significant gaps remain in understanding the mediating role of emotion regulation in these relationships. Amis: The present study aimed to investigate the mediating role of emotion regulation in the relationship between attachment styles, social skills, and anxiety in children with autism spectrum disorder. Method: This correlational study utilized structural equation modeling. The statistical population included all children with ASD in Kermanshah during the academic year 2023-2024. From this population, 200 children were selected through convenience sampling based on inclusion and exclusion criteria. Data were collected using the Middle Childhood Attachment Questionnaire (Ronaghi et al., 2013), Social Skills Questionnaire (Bellini & Hopf, 2007), Emotion Regulation Questionnaire (Shields & Cicchetti, 1997), and Anxiety Scale (Rogers et al., 2016). Data analysis was conducted using SPSS-24 and Amos-24 software. Results: Results indicated that more secure attachment styles were associated with increased social skills (β= 0.382) and decreased anxiety (β= -0.138) in children with ASD. Additionally, emotion regulation mediated the relationship between attachment style and social skills (β= 0.067) and between attachment style and anxiety (β= -0.029) (p< 0.05). Conclusion: It is recommended that appropriate intervention programs be designed by specialists and implemented in exceptional centers and schools for children with autism spectrum disorder. Additionally, family education workshops (especially for mothers/caregivers) should be organized, focusing on the role of attachment styles in social skills and anxiety in children with autism spectrum disorder.